A 9, 9′-spirobi[9H-fluorene]-cored perylenediimide derivative and its application in organic solar cells as a non-fullerene acceptor. Issue 8 (14th December 2015) - Yi, Jinduo; Wang, Yiling; Luo, Qun; Lin, Yi; Tan, Hongwei; Wang, Hongyu; Ma, Chang-Qi
Abstract : A structurally orthogonal molecule (SBF-PDI4 ) with a 9, 9′-spirobi[9 H -fluorene] (SBF) core and four perylenediimide (PDI) at periphery was developed for use in polymer solar cells. Proper LUMO energy level (−4.1 eV) and good light absorption ability over 450–550 nm make it an excellent non-fullerene acceptor. Abstract : A structurally non-planar molecule (SBF-PDI4 ) with a 9, 9′-spirobi[9 H -fluorene] (SBF) core and four perylenediimides (PDIs) at the periphery was designed, synthesized and characterized. This compound shows a low-lying LUMO energy level of −4.11 eV, which is similar to that of PCBM, but with intensive light absorption ability in the range 450–550 nm. A high power conversion efficiency (PCE) of 5.34% was obtained for a solution processed bulk heterojunction solar cell (BHJSC) usingSBF-PDI4 as the electron acceptor and a low-band gap polymer poly[[4, 8-bis[5-(2-ethylhexyl)thiophene-2-yl]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl]] (PTB7-Th) as the electron donor. These results demonstrate that PDI derivatives with a three dimensional molecular structure could serve as high performance electron acceptors in BHJSCs.